Fatores que afetam o transporte urbano de carga: uma proposta de banco de dados - Prieto, Ana Carolina Falkembach (Universidade Federal de São Carlos, 2021)
This work aims to develop a database to support stakeholders who participate in urban freight transport to analyze the main factors that can affect the transport of their cargo. Considering the growth of urban centers and, consequently, the demand for goods, it is possible to identify 4 main groups of factors that affect urban mobility: logistical, regulatory, environmental, and risky. The database is designed for the São Paulo Metropolitan Region. Its methodology is divided into four stages: the Requirements Analysis identifies the main information that will make up the database; the Conceptual Model is implemented through an Entity-Relationship Model; the Logic Model defines how the database will be implemented in a database management system; and, the Physical Model is implemented in SQL language. The database makes it possible to register data referring to the factors and, therefore, allows information to be extracted, through queries, through a single database. Based on the database information, it is possible for agents to anticipate factors, reducing unforeseen events and increasing their efficiency and reliability.
Factors of the urban freight transport: a database proposal
Keywords: Banco de dados; Transporte urbano de carga; Logística; Database; Urban freight transport; Logistic; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES